دور الناخب في عملية الترشح - كشحة, محمد الصالح (جامعة الوادي.University eloued, 2021)
يعرف الناخب بأنه الشخص المسجل بالقائمة الانتخابية لجميع الأشخاص الذين يتوفر فيهم حق التصويت ، ويمكنهم من ممارسة سلطة الاختيار في إطار العملية الانتخابية ، ويشترط فيه أن يكون مسجلا بالقائمة الانتخابية ، التي تتطلب توفر شرط السن المقدر ب18 سنة كاملة يوم الانتخاب ، وأن يكون حاملا الجنسية الجزائرية ، بالإضافة إلى التمتع بالحقوق المدنية والسياسية . كما يلعب الناخب دورا بارزا في عملية الترشح وخاصة في جمع التوقيعات ، فلا يمكن الاستغناء عنه تحت طائلة البطلان وعدم قبول الترشح وهو ما يتطلب توفر العدد المطلوب من التوقيعات، خاصة في انتخابات رئيس الجمهورية ، أما بالنسبة لانتخابات المجلس الشعبي الوطني و المجالس المحلية، فيمكن أن تحل محلها عملية التزكية التي يبقى فيها دور الناخب محوريا ، كما يبرز دور الناخب في الطعون القضائية التي : The voter is defined as the person registered in the electoral list of all persons who have the right to vote, and which enables them to exercise the power of choice within the framework of the electoral process. To be registered in the previous list, it is required to be 18 years olden the date of the election, be of Algerian nationality, and enjoy civil and political rights. The voter plays a prominent role in this candidacy process, especially in collecting signatures. He cannot be replaced under penalty of nullity or because of the rejection of his candidacy. This required the needed number of signatures, especially in the presidential election. For the election of the national popular council and the local councils, it can be replaced by the acclamation process where the role of the voter remains primordial. The role of the voter appears also in the judicial appeals which were not directly identified, except in the framework of those whose candidacy was rejected. For the rest of the candidates and voters, the judicial appeal validity remains general in the framework of the appellant's eligibility and the realization of direct interest. As a result, the voter cannot exercise his right, and it constrains him and affects the exercise of popular control and the electoral process. Besides, the administration exercises arbitrarily this authority and monopolizes the exercise of this right on those whose candidacy was rejected directly. keywords: Voter, electoral list, candidacy, signatures, judicial appeals.
مجلد 12 العدد 02
Keywords: الناخب ، القائمة الانتخابية ، الترشح ، التوقيعات ، الطعون القضائية; Voter, electoral list, candidacy, signatures, judicial appeals